Analysis Of Key Factors Influencing Behavioral Intention To Adopt Cryptocurrency In Indonesia: A Demographic Perspective - I Gede Artha Juan Christian Lie; Taufik Faturohman (UNIVED Press, 2025)
This study examines the key factors influencing the behavioral intention to adopt cryptocurrency in Indonesia from a demographic perspective. Utilizing descriptive statistics and non-parametric tests such as the Mann-Whitney U Test and Kruskal-Wallis Test, the research analyzes how gender, age, educational level, and occupation impact individuals' perceptions and intentions regarding cryptocurrency adoption. The findings reveal significant differences across these demographic groups, particularly in areas such as financial literacy, perceived risk, social influence, and awareness. Males, younger individuals, and those with higher education levels or finance-related occupations exhibit a stronger intention to adopt cryptocurrency, driven by lower perceived risks and higher financial literacy. Conversely, females, older adults, and those with lower education levels show more hesitation, primarily due to higher perceived risks and lower awareness. The study underscores the need for targeted educational initiatives and policy interventions to address these demographic disparities and promote a more inclusive adoption of cryptocurrency in Indonesia. These insights are crucial for developing effective strategies to support the growth of cryptocurrency as part of the digital economy.